The African Proverbs Project and After - Mbiti, John S. (Lexikos, 2002)
Abstract: The Pew Charitable Trusts financed the African Proverbs Project with Dr Stan Nussbaum as co-ordinator, for three years (1993?1996). He assembled a number of scholars who had collected and studied proverbs. The purpose of the Project was to encourage further work of collecting, studying and publishing proverbs. It organised international and interdisciplinary symposia and embarked on three types of publications. One kind of publication was the African Proverbs Series, with Prof. John Mbiti as editor. Five volumes were published in 1997, each with proverbs from respectively Ethiopia, Uganda, Lesotho, Burkina Faso and Ghana. Their size ranged from 584 to 1 497 proverbs in African languages, with translations into English or French. Another set of publications with the Rev. Joshua Kudadjie as editor, covered proverbs for preaching and teaching purposes. Three volumes have come from Malawi, Ghana and Liberia. The Project also published an annotated bibliography by Prof. Wolfgang Mieder. The report from one of the symposia appeared in 1997. The third manner of publication is in the form of a CD-ROM edited by Dr Stan Nussbaum and published in 1996. This is a very comprehensive collection and source of material that includes, inter alia, books from the Project, some 28 000 proverbs, a bibliography with 1 000 items, summaries and extracts from published collections, and a language survey of work on proverbs. The Project has generated both local and international interest in African paremiography and paremiology. Four academic institutions in South Africa, Kenya, Ghana and the Ivory Coast, with links to others in Africa, Europe and America, are continuing this work on proverbs. Keywords: AFRICAN PROVERBS PROJECT, AFRICAN PROVERBS SERIES, PROVERB, PAREMIOGRAPHY, PAREMIOLOGY Opsomming: Die African Proverbs Project en daarna. Die Pew Charitable Trusts het die African Proverbs Project, met dr. Stan Nussbaum as ko?rdineerder, vir drie jaar (1993?1996) gefinansier. Hy het ’n aantal vakkundiges bymekaargebring wat spreekwoorde versamel en bestudeer het. Die doel van die projek was om verdere werk ten opsigte van die versameling, bestudering en publikasie van spreekwoorde aan te moedig. Dit het internasionale en interdissiplin?re simposia georganiseer en drie soorte publikasies onderneem. Een soort publikasie was die African Proverbs Series, met prof. John Mbiti as redakteur. Vyf bande is in 1997 gepubliseer, elkeen met spreekwoorde van onderskeidelik Ethiopi?, Uganda, Lesotho, Burkina Faso en Ghana. Hul omvang het gewissel van 584 tot 1 497 spreekwoorde in Afrikatale, met vertalings in Engels en Frans. ’n Ander stel publikasies, met eerw. Joshua Kudadjie as redakteur, het spreekwoorde vir preek- en onderwysdoeleindes gedek. Drie dele is afkomstig van Malawi, Ghana en Liberi?. Die projek het ook ’n geannoteerde bibliografie deur prof. Wolfgang Mieder gepubliseer. Die verslag van een van die simposia het in 1997 verskyn. Die derde manier van publikasie is in die vorm van ’n CD-ROM, deur dr. Sam Nussbaum geredigeer en in 1996 gepubliseer. Dit is ’n baie omvattende versameling en bron van materiaal wat onder andere boeke van die projek, ongeveer 28 000 spreekwoorde, ’n bibliografie met 1 000 items, opsomming en uittreksels van gepubliseerde versamelings en ’n taaloorsig van werk oor spreekwoorde insluit. Die projek het sowel plaaslike as internasionale belangstelling in die paremiografie en paremiologie van Afrika gewek. Vier akademiese instellings in Suid-Afrika, Kenia, Ghana en die Ivoorkus met skakels met ander in Afrika, Europa en Amerika, sit hierdie werk oor spreekwoorde voort. Sleutelwoorde: AFRICAN PROVERBS PROJECT, AFRICAN PROVERBS SERIES, SPREEKWOORD, PAREMIOGRAFIE, PAREMIOLOGIE